Pengaruh Pengumuman Stock Split terhadap Return Saham Perusahaan Pemecah Saham dan Bukan Pemecah Saham pada Sektor Industri yang Sama Di BEI: Pengujian Efek Contagion dan Competitive - Kusharyanti Kusharyanti; Sri Astuti (Jurnal Akuntansi dan Bisnis, 2008)
The objectives of this research were to know and analyse information transfer over industries in the announcement of stock split, kinds of information transfer whether contagion or competitive effect, and the effect of industry factor and company specific on the stock split transfer information. This research was developed from prior research by Tawatnuntachai and D’Mello (2002). The first and second hypotheses were examined using one-sample-difference test and the third hypothesis was examined using multi regression test. The research years were from 1997 until 2003. The research used 52 reporter firms sample and 272 match sample of non reporter firms. The result of study showed that the first and the second hypotheses were accepted. Stock split announced by firms oppositely affected the return of non reporter firms. Test on the third hypothesis prove that only abnormal return variable and the size of reporter firms which significantly affected the amount of stock split transfer information. While other variables such as error on pricing, level of information asymmetry, and split factor did not affect.